2012
DOI: 10.1002/hyp.9361
|View full text |Cite
|
Sign up to set email alerts
|

Factors controlling diurnal variation in the isotopic composition of atmospheric water vapour observed in the taiga, eastern Siberia

Abstract: Deciduous forest covers vast areas of permafrost under severe dry climate in eastern Siberia. Understanding the water cycle in this forest ecosystem is quite important for climate projection. In this study, diurnal variations in isotopic compositions of atmospheric water vapour were observed in eastern Siberia with isotope analyses of precipitation, sap water of larch trees, soil water, and water in surface organic layer during the late summer periods of 2006, 2007, and 2008. In these years, the soil moisture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…The isotopic proportions of water‐derived hydrogen and oxygen were analyzed by the CO 2 /H 2 /H 2 O equilibration method using Delta V (Thermo Fisher Scientific, USA, manufactured in Germany) attached to a Gas Bench (Thermo Fisher Scientific, USA) at Hokkaido University, Japan (e.g. Ueta et al ., ). The data were expressed as δ D or δ 18 O values, defined as δ Sample (‰) = ( R Sample / R VSMOW − 1) × 1000, where R is the isotope ratio of water (D/H or 18 O/ 16 O), and subscripts Sample and VSMOW refer to samples and Vienna Standard Mean Ocean Water, respectively.…”
Section: Methodsmentioning
confidence: 97%
“…The isotopic proportions of water‐derived hydrogen and oxygen were analyzed by the CO 2 /H 2 /H 2 O equilibration method using Delta V (Thermo Fisher Scientific, USA, manufactured in Germany) attached to a Gas Bench (Thermo Fisher Scientific, USA) at Hokkaido University, Japan (e.g. Ueta et al ., ). The data were expressed as δ D or δ 18 O values, defined as δ Sample (‰) = ( R Sample / R VSMOW − 1) × 1000, where R is the isotope ratio of water (D/H or 18 O/ 16 O), and subscripts Sample and VSMOW refer to samples and Vienna Standard Mean Ocean Water, respectively.…”
Section: Methodsmentioning
confidence: 97%
“…Studies of the isotopic distribution in atmospheric water vapour, precipitation, sap water, and soil water have led to an improved understanding of continental water circulation and enabled the estimation of the contribution of transpiration fluxes to atmospheric water vapour in forest ecosystems (Dawson et al, 2002;Li et al, 2007;Plamboeck et al, 1999;Sugimoto et al, 2003). The stable isotopic compositions of water in trees and their surrounding soil has revealed the primary water sources of trees (Busch et al, 1992;Dawson, 1998;Dawson and Ehleringer, 1991;Tsujimura et al, 2007;Ueta et al, 2012) and clarified the distinguishing characteristics of these sources for plants in permafrost ecosystems (Sugimoto et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Under a high temperature condition, active plant transpiration is expected, which returns a water vapour with high δ 18 O to the atmosphere. Our previous study on diurnal variation of atmospheric water vapour has been revealed that plants transpire the water vapour with δ 18 O ranging from −17·9 to −13·3‰, which was much higher than those of atmospheric water vapour (Ueta et al ., ). Taking into consideration that the study site locates in the vast forested area in eastern Siberia, it is quite reasonable that plant transpiration was attributable to the high δ 18 O, when plant transpiration was active under warm condition.…”
Section: Discussionmentioning
confidence: 97%
“…(). Precipitation, plant sap water, soil water and water in surface organic layer were also sampled, and data for those were described in Ueta et al ., (in press) as well.…”
Section: Observation and Analysismentioning
confidence: 99%
See 1 more Smart Citation